Combined Application of Percutaneous Extracorporeal Lung Assistance System Together with Catheter-Directed Therapy for the Rescue of Massive Pulmonary Embolism after Failed Systemic Thrombolysis - Eva-Maria Brandner; Armin Huber; Karl-Ludwig Laugwitz; Tareq Ibrahim (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
A 56 year-old, formerly healthy man, who had undergone surgery of the shoulder joint earlier that same day, was presented at our department with a sudden onset of severe dyspnea and thoracic pain. Clinical fi ndings were central cyanosis, a heart rate of 120 bpm, a blood pressure of 100/70 mmHg and a decreased peripheral oxygen saturation of 89%. Prompt computed tomography revealed a massive,  bilateral pulmonary embolism (Figure 1a-c).